Wielerella bovis gen. nov., sp. nov. a member of the family Neisseriaceae associated with bovine endocarditis. Issue 5 (11th May 2022) - Kuhnert, Peter; Brodard, Isabelle; Bock, Sabine; Hemphill, Andrew; Akarsu, Hatice; Engelhardt, Andreas; Kutzer, Peter
Abstract : Seven bacterial strains isolated from bovine endocarditis in six animals from different geographic regions were investigated in a polyphasic taxonomic approach. Phylogenetic analysis based on 16S rRNA gene sequences placed all seven isolates on a distinct, monophyletic cluster in the family Neisseriaceae with closest similarity to type strains of Alysiella filiformis (97.06 %) and Kingella kingae (96.34 %). Whole genome sequence analysis of isolates confirmed their species status, with an average nucleotide identity >96 % between isolates and <80 % to other type species of genera of Neisseriaceae while digital DNA–DNA hybridization values were >80 % and<18 %, respectively. The DNA G+C content was 42.5–43.0 mol%. Whole genome sequence based phylogeny showed the isolates being monophyletic and separated from established genera, thereby forming a new genus within the family Neisseriaceae . Similarly, analysis of MALDI-TOF MS reference spectra clustered the isolates close together and clearly separated from other genera, making this the method of choice for identification. Biochemical markers based on classical as well as commercial identification schemes allowed separation from closely related Neisseriaceae genera, even though the new taxon is biochemically not very active. Major fatty acids are C12 : 0, C14 : 0 and C16 : 0 . The major quinone is ubiquinone Q-8. In the polar lipid profile, diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and phospholipid were predominant. We propose the novel genus Wielerella with the type species Wielerella bovis gen. nov., sp. nov. The type strain is CCUG 44465 T (=DSM 113289 T =JF 2483 T ) isolated post mortem from a cow with endocarditis in Switzerland.